EFFECT OF INTEGRATED NUTRIENT MANAGEMENT ON POTATO AND ITS RESIDUAL EFFECT ON SUCCEEDING MOONG CROP UNDER IRRIGATED CONDITION OF SOUTH BIHAR - Singh, S. K.; Lal, S. S.; Dua, V. K. (Potato Journal, 2013)
A field experiment was conducted at Patna during winter and summer seasons of 2003-04 and 2004-05 on sandy clay loam soil low. The trial on potato was laid out in randomized block design and that of moong in split plot design with three replications. The tuber yield of potato increased significantly with increase in fertility levels from 75% recommended dose of fertilizers (RDF) to 100% RDF. Highest tuber yield and total dry matter production, NPK uptake and net return were recorded with integrated application of FYM @ 15 t /ha + 100% RDF followed by 100% RDF + crop residue + bio-fertilizer. Application of FYM@15 t/ha + 75% RDF recorded significantly higher tuber yield over 75% RDF alone but remained at par with 100% RDF. Highest value of all the yield attributes and grain yield of moong was observed with the residual effect of combined application of 100% RDF + FYM @ 15 t/ha. Direct effect of NPK application to moong was more pronounced over residual effect. Yield attributes, grain yield and net return improved significantly with each increment of NPK from 50% RDF to 100% RDF. Nutrient management practices brought about significant variation in organic carbon, phosphorous and nitrogen status of soil and non-significant variation in K status at harvest. Highest improvement in soil fertility was observed with application of FYM @15t/ha +100% RDF followed by 100% RDF + biofertilizer + crop residue incorporation.